2012
DOI: 10.1111/j.1540-5885.2012.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Social Contagion during New Product Adoption

Abstract: Social contagion has been shown to play an important role during new product adoption by consumers. Social contagion is the process by which consumers influence each other to adopt and use a product in a specific way. Current literature makes a basic assumption that social contagion is caused by the characteristics of consumers, who they interact with or who they live near to, and thus are most likely to come into contact with. However, the role that the product has in stimulating social contagion is conspicuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 61 publications
3
36
0
Order By: Relevance
“…10, No. 7;2015 18-24, 25-34, 35-44 and 45 or above is 5.13, 5.07, 4.95 and 5.06 respectively, indicating that age does not affect the behavior intention of consumers using mobile commerce services in Hong Kong. As there are no significant differences in the mean values of different subgroups in terms of gender, marital status, education level and age, all that data could be analyzed as a whole.…”
Section: Control Variablesmentioning
confidence: 95%
See 1 more Smart Citation
“…10, No. 7;2015 18-24, 25-34, 35-44 and 45 or above is 5.13, 5.07, 4.95 and 5.06 respectively, indicating that age does not affect the behavior intention of consumers using mobile commerce services in Hong Kong. As there are no significant differences in the mean values of different subgroups in terms of gender, marital status, education level and age, all that data could be analyzed as a whole.…”
Section: Control Variablesmentioning
confidence: 95%
“…Compatibility is defined as the degree to which using mobile commerce services is perceived as being consistent with the user's existing lifestyle, values, needs and preferences (Chen, Gillenson, & Sherrell, 2002;Langley, Bijmolt, Ortt, & Pals, 2012). Chen, Gillenson and Sherrell (2002) found that compatibility has a positive influence on consumer behavior in online shopping.…”
Section: Behavior Intentionmentioning
confidence: 99%
“…A new brand can increase the entire market potential due to its promotion or compete for the same market potential and slow down diffusion [20]. Given the role of social contagions in the process of innovation [21], synergy quantification frames cooperation and competition in precise, numerical terms consider general purpose technologies (GPTs). GPTs are technologies that have an impact across sectors and spillover effects as network externalities with economic benefits [22].…”
Section: Introductionmentioning
confidence: 99%
“…According to Cialdini (2008), influence occurs through six mechanisms: reciprocity, commitment and consistency, social proof, authority, liking, and scarcity. Contagion, or social contagion, is similar to influence but adopts the metaphor of viral infection such that the focus is on the behavior that makes use of people to propagate itself (Du and Kamakura, 2011;Langley et al 2012). Influence and contagion are two processes with the focus at the individual level.…”
Section: Comparing Herding To Diffusion Influence and Contagionmentioning
confidence: 98%